2021
DOI: 10.1371/journal.pone.0248334
|View full text |Cite
|
Sign up to set email alerts
|

Trust predicts COVID-19 prescribed and discretionary behavioral intentions in 23 countries

Abstract: The worldwide spread of a new coronavirus (SARS-CoV-2) since December 2019 has posed a severe threat to individuals’ well-being. While the world at large is waiting that the released vaccines immunize most citizens, public health experts suggest that, in the meantime, it is only through behavior change that the spread of COVID-19 can be controlled. Importantly, the required behaviors are aimed not only at safeguarding one’s own health. Instead, individuals are asked to adapt their behaviors to protect the comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
227
5
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 189 publications
(252 citation statements)
references
References 48 publications
16
227
5
4
Order By: Relevance
“…They are also in line with previous works showing that perceived threat related to COVID-19 tended to increase success for conservative political parties in France [ 31 ], but also with the model of political conservatism as motivated social cognition showing that fear of threat and loss positively predict political conservatism [ 50 ]. Furthermore, interestingly, Pagliaro et al [ 51 ] found that the actual threat posed by COVID-19 (deaths per million people) did not significantly predict individuals’ compliance with preventive behaviors. Our results thus point to the importance to distinguish perceived (in our study) and actual (Pagliaro et al’s [ 51 ] study) threat when it comes to consider the links between threat and compliance with movement restrictions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also in line with previous works showing that perceived threat related to COVID-19 tended to increase success for conservative political parties in France [ 31 ], but also with the model of political conservatism as motivated social cognition showing that fear of threat and loss positively predict political conservatism [ 50 ]. Furthermore, interestingly, Pagliaro et al [ 51 ] found that the actual threat posed by COVID-19 (deaths per million people) did not significantly predict individuals’ compliance with preventive behaviors. Our results thus point to the importance to distinguish perceived (in our study) and actual (Pagliaro et al’s [ 51 ] study) threat when it comes to consider the links between threat and compliance with movement restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, interestingly, Pagliaro et al [ 51 ] found that the actual threat posed by COVID-19 (deaths per million people) did not significantly predict individuals’ compliance with preventive behaviors. Our results thus point to the importance to distinguish perceived (in our study) and actual (Pagliaro et al’s [ 51 ] study) threat when it comes to consider the links between threat and compliance with movement restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…The overall equation was significant, R 2 = 0.31, F(4, 303) = 34.89, p < 0.000. Crucially for the present purpose, the job demands by non-acceptance interaction significantly increased the explained variance [∆R 2 Globally, the three dimensions of stigma towards customers (fear, discrimination and not acceptance) affect the relationship between Job demand and fatigue at different levels [Hp2a confirmed; see Table 2]. ∆R 2 = 0.02 *** Supported…”
Section: Fatigue As An Outcomementioning
confidence: 95%
“…The conceptualisation of stigma has an extensive background; it is defined as a social process characterised by stereotyping, labelling, avoiding and discrimination towards specific categories or individuals [41]. The rapid spread of SarsCov2 saw a concurrent rise in feelings of fear and distrust that gradually overwhelmed entire countries around the world, with the increase in infections, restrictive measures to avoid infections and constantly updated media information [2].…”
Section: Social Stigma Fear For Covid-19 and Frontline Workersmentioning
confidence: 99%
See 1 more Smart Citation